2013
DOI: 10.1371/journal.pone.0070310
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of First Venous Thromboembolism in and around Pregnancy Using Linked Primary and Secondary Care Data: A Population Based Cohort Study from England and Comparative Meta-Analysis

Abstract: BackgroundRecent linkage between primary and secondary care data has provided valuable information for studying heath outcomes that may initially present in different health care settings. The aim of this study was therefore, twofold: to use linked primary and secondary care data to determine an optimum definition for estimating the incidence of first VTE in and around pregnancy; and secondly to conduct a systematic literature review of studies on perinatal VTE incidence with the purpose of comparing our estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 31 publications
2
32
1
Order By: Relevance
“…A total of 150 papers were selected for full‐text review, of which three were added to the search results based on our previous knowledge. Full‐text review led to the exclusion of 102 papers for the reasons stated in Figure , including four articles that were excluded because they only reported composite outcomes, aggregating the frequency of multiple conditions in the WHO list . We selected 48 eligible systematic reviews, and from searching their references we found one more.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 150 papers were selected for full‐text review, of which three were added to the search results based on our previous knowledge. Full‐text review led to the exclusion of 102 papers for the reasons stated in Figure , including four articles that were excluded because they only reported composite outcomes, aggregating the frequency of multiple conditions in the WHO list . We selected 48 eligible systematic reviews, and from searching their references we found one more.…”
Section: Resultsmentioning
confidence: 99%
“…Certain delivery‐related factors (eg, the prothrombotic state) could have substantial impact on the occurrence of ischemic stroke in the high‐risk period. Previous research has found that the risk of first venous thromboembolism is also significantly higher around the time of delivery and early postpartum . In addition, other risk factors unique to pregnancy, such as pregnancy‐induced hypertension and preeclampsia or eclampsia, especially increase the risk of hemorrhagic stroke .…”
Section: Discussionmentioning
confidence: 99%
“…In the United Kingdom, stillbirth is defined as a baby deceased after 24 completed weeks of pregnancy. Women's follow‐up time between ages 15 and 49 years was divided into time associated with pregnancy (defined from the date of conception until 12 weeks postpartum) and nonpregnant time (all other available follow‐up time, which included all time for women who were never pregnant during the study period, as previously defined).…”
Section: Methodsmentioning
confidence: 99%
“…Only the first validated instance of VTE was included in the analysis. The definition using primary care data alone has been validated previously; 84 per cent of cases were valid and used in previous studies of VTE.…”
Section: Methodsmentioning
confidence: 99%